Hubungan Tingkat Kecemasan Dengan Siklus Menstruasi Pada Remaja Siswi Dismk Trinita Manado - Harimu, Pramuti; Legi, Julita (Journal Of Community & Emergency, 2024)
dolescence is the transition from puberty to adulthood. During this period, adolescents experience many changes, both physically, psychologically, and socially. Individuals are said to have entered adolescence between the ages of 16 or 17 years and ended at the age of 21 years. The purpose of the study was to determine the relationship between the level of anxiety and the menstrual cycle in adolescent girls at SMK Trinita Manado. This type of research uses quantitative methods with a cross sectional study approach, the sample in this study uses purposive sampling technique, the number of samples is 112 respondents. The results of statistical tests using the chi-square test obtained the value of -value = 0.001 which is smaller than the value of = 0.05, meaning that H0 is rejected, so there is a significant relationship between Anxiety Levels and Menstrual Cycles in Teenage Girls at SMK Trinita Manado. mild anxiety with regular menstrual cycles as many as 42 respondents (24.1%), mild anxiety with irregular menstrual cycles as many as 12 respondents (10.7%), moderate anxiety with regular menstrual cycles as many as 21 respondents (18.8%), anxiety moderate with an abnormal menstrual cycle as many as 13 respondents (11.6%), severe anxiety with a regular menstrual cycle as many as 8 respondents (7.1%), severe anxiety with an abnormal menstrual cycle as many as 16 respondents (14.3%). This study concludes that the level of anxiety in adolescent girls at SMK Trinita Manado is mostly severe anxiety levels, the menstrual cycle in adolescent students at SMK Trinita Manado has irregular menstrual cycles and there is a relationship between anxiety levels and menstrual cycles in adolescent students at SMK Trinita Manado. Suggestion: This research can increase knowledge for students in managing anxiety levels so that they can facilitate menstruation